Graphic Information Processing Technology and its Importance - Olimov, Shirinboy Sharofovich; Mamurova, Dilfuza Islomovna (European Journal of Life Safety and Stability (2660-9630), 2021)
The very rapid development of information and communication technologies and the means of their implementation predetermines the formation of the information society. working with computer graphics in computer technology is becoming one of the most popular areas. Even professional artists and designers are engaged in this direction. It is important for any professional to get acquainted with computer graphics and their types, as well as to improve their skills.